EDUKASI MENINGKATKAN EMOTIONAL INTELLIGENCE UNTUK MEMAKSIMALKAN KINERJA DI TENGAH KONDISI PANDEMI COVID 19 - Siti Djauharoh; P. Tommy Y.S. Suyasa (PROSIDING SERINA, 2021)
The effects of the COVID- 19 pandemic have made changes in both behavior and even work systems. One of them is the work was stopped due to regulations imposed by the government for activity restrictions. So that some sectors of work stopped. As a result of this regulation, the situation became uncertain. This causes the company's revenue to decrease. This also makes employees nervous because it is difficult to get projects and they are worried that layoffs will occur. So that their performance is not optimal because they are filled with anxiety thinking about this uncertain situation. Whereas employee performance is one of the factors that determine the effectiveness of the company. Performance is closely related to the quality of work of employees because performance is also determined based on the ability of employees to manage stress. So that the results of the work are not optimal which causes complaints to customers. Even in the midst of this pandemic situation, employees need to make adjustments in the face of the uncertainty of this condition. Community Service Activities at PT X aim to provide knowledge to employees about actions that can be taken to overcome difficulties and uncertainties at work by increasing employees' emotional intelligence. This activity is expected to improve employee performance. This activity was carried out during a pandemic situation so that it was not possible to do face-to-face meetings. As a solution, this activity is finally carried out virtually through the zoom application. The results of the PkM evaluation indicate that this activity has an impact on increasing employee knowledge about how to overcome difficulties and uncertainties at work so that employees can work comfortably and provide their best performance in carrying out their duties. We also hope that this PkM output can help employees have better performance so that it will have an impact on the development of the company for the better.